2017
DOI: 10.11607/ijp.4929
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes for Mandibular Mini-Implant–Retained Overdentures: A Systematic Review

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 0 publications
6
27
0
Order By: Relevance
“…No significant differences regarding cumulative 1‐year survival rate, both at the implant level and at the patient level between the Short‐ and the Standard‐MDI groups indicate good clinical behavior of short MDIs. Survival rates obtained in this study for the both groups are in accordance with other reports for standard length MDIs (Elsyad, ; Elsyad et al, ; Goiato et al, ; Griffitts et al, ; Hasan et al, ; Klein et al, ; Lemos et al, ; Marcello‐Machado, Faot, Schuster, Nascimento, & Del Bel Cury, ; Mundt, Schwahn, Biffar, & Heinemann, ; Mundt, Schwahn, Stark, et al, ; Park, Lee, & Shin, ; Peršić et al, ; Scepanovic et al, ; Šćepanović et al, ; Schiegnitz & Al‐Nawas, ; de Souza et al, ; Zygogiannis et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…No significant differences regarding cumulative 1‐year survival rate, both at the implant level and at the patient level between the Short‐ and the Standard‐MDI groups indicate good clinical behavior of short MDIs. Survival rates obtained in this study for the both groups are in accordance with other reports for standard length MDIs (Elsyad, ; Elsyad et al, ; Goiato et al, ; Griffitts et al, ; Hasan et al, ; Klein et al, ; Lemos et al, ; Marcello‐Machado, Faot, Schuster, Nascimento, & Del Bel Cury, ; Mundt, Schwahn, Biffar, & Heinemann, ; Mundt, Schwahn, Stark, et al, ; Park, Lee, & Shin, ; Peršić et al, ; Scepanovic et al, ; Šćepanović et al, ; Schiegnitz & Al‐Nawas, ; de Souza et al, ; Zygogiannis et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…The results of the study revealed non-significant difference between both groups regarding the first part of questionnaire (related to phonetics and esthetics) which support the null hypothesis that as long as there is no significant difference between the two treatment modalities so it is preferred to rely on the minimal simple treatment of edentulous mandible (two mini-implant) to decrease surgical intervention, time and cost of the treatment 9 .…”
Section: Discussionmentioning
confidence: 64%
“…Edentulous patients can be rehabilitated satisfactorily through implant-retained overdentures, eliminating problems common to conventional denture users, such as pain, decreased bite force (1), unsatisfactory retention, stability, aesthetic and phonetic (2), that too much compromise masticatory function (1). Thus, this type of prosthesis provides fewer injuries to the supporting tissues and more comfort to patients and increases their satisfaction with the rehabilitation treatment (3,4).…”
Section: Introductionmentioning
confidence: 99%